Effectiveness of Teachers in Implementing School Budget Activity Planning - Nur Hayati (Al-Qalam Institue, 2025)
School Activity Budget Planning (RKAS) is an important instrument in education management that aims to ensure the effectiveness of the teaching and learning process and the efficiency of fund use. In the context of school autonomy and demands for transparency, teacher involvement in the preparation of RKAS is crucial. However, low budget literacy and limited technical training are still obstacles in its implementation. This study aims to explore the effectiveness of the role of teachers in RKAS planning and analyze the contribution of principal leadership and management of supporting resources. This study uses a qualitative approach with a case study design, through in-depth interview techniques, participant observation, and documentation studies. The results of the study indicate that teacher effectiveness in RKAS planning is influenced by the clarity of leadership vision, availability of infrastructure, and professional development programs. These findings emphasize the importance of collaboration and strengthening teacher capacity in creating participatory and sustainable education budget management.